2020
DOI: 10.1016/j.jped.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of children with acute lymphoblastic leukemia in a middle-income developing country: high mortalities, early relapses, and poor survival

Abstract: There was a high incidence of induction deaths related to infection and high percentages of very early/early relapses, with high mortalities and low 5-year overall survival rates. These findings suggest the urgent need for modification of chemotherapy regimens to be suitable for the local conditions, including implementation of supportive care and infection control policies. There is also a requirement for antimicrobial prophylaxis during induction period combined with the necessary increase in government heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
51
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 26 publications
(34 reference statements)
16
51
1
5
Order By: Relevance
“…ALL is the commonest childhood malignancy and the 5‐year event‐free survival (EFS) is now approaching 90% in developed countries . However, the survival outcome is still suboptimal in developing countries . A recent multicenter study from China reported 5‐year EFS of 79.9% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALL is the commonest childhood malignancy and the 5‐year event‐free survival (EFS) is now approaching 90% in developed countries . However, the survival outcome is still suboptimal in developing countries . A recent multicenter study from China reported 5‐year EFS of 79.9% .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, the survival outcome is still suboptimal in developing countries. 8,9 A recent multicenter study from China reported 5-year EFS of 79.9%. 10 most important cause of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…The much higher L2 and high risk prevalence comparing to other studies may reflect an underlying cause, such as from war or environment as many practices in Syria may contain leukemogenesis such as unprotected pesticide usage, mate drinking and hookah smoking, mainly in low educational level population 24 . It is suggested that the protocols that were developed in the advanced centres might increase the rate of death as these protocols are not adjusted to the local conditions of low-and mid-income countries 2,3 , and therefore more studies are required in developing countries such as Syria for adjustment of protocols that change ALL variables. Although the cost of treatment in Syria is covered, there is data suggesting that families within low SES are correlated with worse prognosis in children as determination of indirect costs is difficult 8 which can explain having lower educational parents was correlated with poorer prognosis in our study.…”
Section: Symptoms Fbc and Organomegaly Most Patients Presented Withmentioning
confidence: 99%
“…Although ALL is curable, many parts of the world may not have access to modern treatment. Approximately eight to nine of every ten children that have ALL are considered long-term survivors and cured in developed countries, but these reults markedly differ in developping countries 2,3 . These positive outcomes are due to having access to top treatments at the most advanced institutions 2 .…”
mentioning
confidence: 99%
“…In recent years, with the gradual improvement of chemotherapy regimens and the progress of individualized treatment, the complete remission rate and long-term disease-free survival rate of childhood acute leukemia has been signi cantly improved (1) . Infection is part of the most important factors causing the death and treatment failure of childhood leukemia therapy (2)(3)(4). Studies have shown that neutrophil de ciency after intensive chemotherapy in leukemia is closely linked to infection-related complications (5).…”
Section: Introductionmentioning
confidence: 99%